Soft energy from palm oil and its wastes - Wong, Kien Keong (Applied Science Publishers, 1981)
A time series analysis of energy sources showed that about 90% of the present energy needs of Malaysia come from petroleum. However, the photosynthetic conversion of sunlight to plant matter has been the supplying energy to man for a long time. Traditionally firewood has been the direct source of photosynthetic energy, but this study proposes that energy can be obtained from the oil palm through the use of its product: the bunches, the fibre, the oil and the mill effluent. A scheme for the bioconversion of palm oil mill effluent through anaerobic digestion is presented. It was found that biogas generated from this process has an energy content of about 24·1 MJ/m3 of gas. The energy equivalent of this for a 60 ton/h mill was calculated at about 180 barrels of oil per day. An energy evaluation of all the wastes from the palm oil fruit was made and it revealed that this can satisfy approximately 17% of Malaysia's energy requirements, thus reducing her dependence upon petroleum. This study also suggests that with rising oil prices it will be appropriate to consider palm oil itself as an alternative fuel in our search for soft energy paths as it can account for about 20% of Malaysia's energy consumption. Developing countries in the tropics which depend heavily on imported petroleum can thus turn to bioconversion energy from the palm oil tree.